HUBUNGAN TINGKAT KETERGANTUNGAN AKTIVITAS KEHIDUPAN SEHARI- HARI DENGAN KUALITAS HIDUP PADA PASIEN PASKA STROKE - Chintia Utami Lyndra; Wasisto " Utomo; Siti " Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract One of disorders caused by stroke is the limitation of activity, so it can affect person’s quality of life. This research was aimed to identify the correlation between level of dependence activity of daily living and quality of life in post stroke patients using correlation research by using cross sectional approach. The samples were 42 stroke patients by using purposive sampling technique. The measurement used were barthel index questionnaire consisting of 10 items of assessment related to the ability to perform activity of daily living and modification questionnaire consisting of 4 domains with a total of 20 items of questions related to quality of life that have been tested validity and reliability with value Cronbach alpha 0,922. The analyses used were univariate analysis dan bivariate analysis by using Kolmogorov-Smirnov test. The research findings that there was a correlation between level of dependence activity of daily living and quality of life in post stroke patients indicated p value (0,00) < α (0,05). Based on the research findings, it is recommended for health’s institution to be able to provide appropriate nursing care adjusted to the patient's condition, so as to improve the quality of life post stroke patient. Keywords : barthel index, level of dependence, quality of life, stroke